PENGARUH PEMBERDAYAAN KARYAWAN, KEMAHIRAN DIRI DAN KETERLIBATAN KARYAWAN TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN (Studi pada Karyawan Politeknik Negeri Sriwjaya) - RINI .; L SUHAIRI HAZIZMA (Program Studi Magister Manajemen FE Unsri, 2013)
This study aims to determine the effect of Employee Empowerment, Self Efficacy and Employee Engagement on Employee Performance Through Job Satisfaction. This study uses data collected through a survey of employees Polytechnic of Sriwijaya. Sampling method in this study using Simple Random Sampling with a sample of 79 respondents. Data analysis using SPSS for Windows version 19 with Path Analysis Method. The independent variable are employee empowerment, self proficiency and employee engagement. While the dependent variable is the job satisfaction and employee performance. The results showed that employee empowerment, self efficacy and work engagement simultaneously have significant effect on job satisfaction. No significant effect of employee empowerment and job satisfaction. Self efficacy have not significant effect on job satisfaction. Work engagement significantly influence job satisfaction. Later, employee empowerment, self efficacy, job involvement, job satisfaction simultaneously have significant effect on employee performance. No significant effect of employee empowerment on employee performance. Self efficacy have significant effect on employee performance. Work engagement significantly influence employee performance. Job satisfaction significantly influence employee performance.